If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 7)(9x + 5) = 0 Reorder the terms: (7 + 6x)(9x + 5) = 0 Reorder the terms: (7 + 6x)(5 + 9x) = 0 Multiply (7 + 6x) * (5 + 9x) (7(5 + 9x) + 6x * (5 + 9x)) = 0 ((5 * 7 + 9x * 7) + 6x * (5 + 9x)) = 0 ((35 + 63x) + 6x * (5 + 9x)) = 0 (35 + 63x + (5 * 6x + 9x * 6x)) = 0 (35 + 63x + (30x + 54x2)) = 0 Combine like terms: 63x + 30x = 93x (35 + 93x + 54x2) = 0 Solving 35 + 93x + 54x2 = 0 Solving for variable 'x'. Factor a trinomial. (7 + 6x)(5 + 9x) = 0Subproblem 1
Set the factor '(7 + 6x)' equal to zero and attempt to solve: Simplifying 7 + 6x = 0 Solving 7 + 6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 0 + -7 6x = 0 + -7 Combine like terms: 0 + -7 = -7 6x = -7 Divide each side by '6'. x = -1.166666667 Simplifying x = -1.166666667Subproblem 2
Set the factor '(5 + 9x)' equal to zero and attempt to solve: Simplifying 5 + 9x = 0 Solving 5 + 9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 9x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 9x = 0 + -5 9x = 0 + -5 Combine like terms: 0 + -5 = -5 9x = -5 Divide each side by '9'. x = -0.5555555556 Simplifying x = -0.5555555556Solution
x = {-1.166666667, -0.5555555556}
| 14.5x= | | =14.5x | | t-2=13 | | (6x+5)(9x+7)=0 | | y=14.5 | | p=2(27)+2(34) | | -1/6(x-18)+(1/3)(x+3)=x-6 | | 4x-32=8x-10 | | n+(n+10)=272 | | -(4y+1)-(-3y-5)=0 | | 3n+4=37 | | x(1x)= | | -1x/9-2=-3 | | 9w=9w+3 | | 5+4r-3=7r+3-2r | | y=1/2(-2)+2 | | 16=-25+n | | 12+n=6 | | 1/4(5x-5)=4 | | x-51=4 | | 22p=198 | | 1.5q-2.8-2.6q=-2.1q-4.7 | | (x+2)(x)(4)=320 | | 7x+12(7)=11 | | 2(a-2)=((a-1)(a-4)) | | 1/2-2/35/6 | | 7x+84=11 | | 6[5-(-3x-9)]=72x+246 | | 12(3x-9)=3(12x+1) | | 3t^2+t=0 | | 2z+3z-z=16 | | 8z-2z+z=14 |